2017
DOI: 10.1590/s0100-204x2017000500003
|View full text |Cite
|
Sign up to set email alerts
|

Associations between vegetative and production traits in guava tree full-sib progenies

Abstract: -The objective of this work was to estimate the genetic parameters and to evaluate the associations between vegetative and yield characteristics, in full-sib progenies of guava tree (Psidium guajava). The following characteristics were evaluated: yield per plant, number of fruits, fruit mass, plant height, stem diameter, and canopy volume. The estimation of genetic parameters was obtained by the REML/Blup procedure. Based on the breeding values predicted by Blup, the genetic and canonical correlations were est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Canonical correlations have been used to elucidate relationships in Saccharum officinarum (Silva et al 2009), Carica papaya (Oliveira et al 2010), guava (Santos et al 2017), Spondias purpurea (Giles et al 2016), Ricinus communis (Brum et al 2011), Triticum sativum L. , Lolium Multiflorum (Müller et al 2012) and Zea mays L. . However there is no information on the associations between groups of traits their simultaneous selection in corn improvement for silage production purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Canonical correlations have been used to elucidate relationships in Saccharum officinarum (Silva et al 2009), Carica papaya (Oliveira et al 2010), guava (Santos et al 2017), Spondias purpurea (Giles et al 2016), Ricinus communis (Brum et al 2011), Triticum sativum L. , Lolium Multiflorum (Müller et al 2012) and Zea mays L. . However there is no information on the associations between groups of traits their simultaneous selection in corn improvement for silage production purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Another answer provided regarding the limitation of ordinary path analysis is that, when no data treatment is undertaken (correction factor in the matrix X'X, data transformation, standardization, and so forth) and data has been given with collinear variables, the incidence of coefficients that exceed the expected limit is common (-1 < 1), such as was seen in the study results of Santos et al (2017), who researched the cause and effect relation between variables of plant growth and yield.…”
Section: Resultsmentioning
confidence: 99%
“…However, indirect selection will not be efficient in providing simultaneous gains for production per plant. To address this problem, it is suggested that simultaneous gains can be achieved through the use of selection-index strategies, as proposed by Cabral et al (2016) and Santos et al (2017).…”
Section: Traitsmentioning
confidence: 99%
“…The mixed-models method has been used to generate information in selective-breeding programs for perennial species such as sugarcane , açaí (Euterpe oleracea) (TEIXEIRA et al, 2012), juçara (Euterpe edulis) (MARÇAL et al, 2015), guava (SANTOS et al, 2017), and passion fruit (SANTOS et al, 2015;SILVA et al, 2016).…”
Section: Introductionmentioning
confidence: 99%